1997
DOI: 10.1074/jbc.272.7.4230
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p130Cas and p105HEF1, a Novel Cas-like Docking Protein, in a Cytoskeleton-dependent Signaling Pathway Initiated by Ligation of Integrin or Antigen Receptor on Human B Cells

Abstract: The Crk-associated substrate p130 Cas (Cas) and the recently described human enhancer of filamentation 1 (HEF1) are two proteins with similar structure (64% amino acid homology), which are thought to act as "docking" molecules in intracellular signaling cascades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 38 publications
4
128
0
Order By: Relevance
“…Ligation of ␤1 integrin receptors induces association of CRKL with CBL, HEF1, or CAS. 29,30 CAS (for Crk-associated substrate) was cloned as a major 130 kDa tyrosine phosphorylated protein in response to v-crk transformation. 27 Currently, there are three CAS-related molecules (the 130 kDa protein CAS, the 110 kDa protein HEF1/CAS-L, 67,68 and the 95 kDa protein SIN/EFS 69,70 ).…”
Section: Cas Hef1mentioning
confidence: 99%
“…Ligation of ␤1 integrin receptors induces association of CRKL with CBL, HEF1, or CAS. 29,30 CAS (for Crk-associated substrate) was cloned as a major 130 kDa tyrosine phosphorylated protein in response to v-crk transformation. 27 Currently, there are three CAS-related molecules (the 130 kDa protein CAS, the 110 kDa protein HEF1/CAS-L, 67,68 and the 95 kDa protein SIN/EFS 69,70 ).…”
Section: Cas Hef1mentioning
confidence: 99%
“…Other reported substrates for PTP-PEST in non-lymphoid cells include Cas (Cote et al, 1998;Garton et al, 1996), Pyk2 and Fak (Lyons et al, 2001). Since many of these same proteins are involved also in integrin signaling and assembly of the immunological synapse in lymphocytes (Manie et al, 1997), it seems likely that PTP-PEST may have a major impact on antigen recognition and T cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports demonstrated that HEF1 is mainly expressed in lymphoid and epithelial cells [2,3]. It has been implicated in signalling pathways initiated by ligation of integrins or antigen on BCR or TCR [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%